Analisis dan Perancangan Sistem Pendukung Keputusan dengan Metode Profile Matching dalam Menentukan Efektifitas Pekerjaan - Aklani, Syaeful Anas; Juzariah, Juzariah (Universitas Internasional Batam, 2017)
Decision support system has become one of the necessities that should be owned in a company which can help to estimate a situation by giving ratings. One of the example is to give assessment on the Job so that it can assist in monitoring the Work and estimate their underlying problems. There are many methods that can be applied in the assessment process one of them is profile matching method, which the assessment process is done by comparing the actual value with the target value has been determined to get value of competence-called gap. The small gap value affects the final value of the calculation method of profile matching where small value gap shows the actual value approaches the target value. Once it is done from the process of ranking the final value obtained to determine the effectiveness of a work.